2022
DOI: 10.3389/fnut.2022.1041065
|View full text |Cite
|
Sign up to set email alerts
|

Birth and newborn care policies and practices limit breastfeeding at maternity facilities in Vietnam

Abstract: The prevalence of early and exclusive breastfeeding in Vietnam remains sub-optimal. The objective of this study was to determine factors associated with early initiation of breastfeeding (EIBF) and exclusive breastfeeding for the first 3 days after birth (EBF3D). We conducted a population-based, cross-sectional survey of 726 mothers with children aged 0–11 months in two provinces and one municipality from May to July 2020. Multinomial logistic regression was used to examine factors associated with EIBF and EBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A potential explanation could be that this hospital is a referral facility that receives clients with high-risk pregnancies within the province and from other provinces in the central part of Vietnam ( 19 ). Cesarean births and vaginal births with episiotomy are barriers to breastfeeding ( 20 22 ). A study from eight countries in the Western Pacific region showed that where mothers received early and uninterrupted skin-to-skin contact in a supportive environment such as rooming-in practice and prohibiting formula use as policy, the breastfeeding rate was still high ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation could be that this hospital is a referral facility that receives clients with high-risk pregnancies within the province and from other provinces in the central part of Vietnam ( 19 ). Cesarean births and vaginal births with episiotomy are barriers to breastfeeding ( 20 22 ). A study from eight countries in the Western Pacific region showed that where mothers received early and uninterrupted skin-to-skin contact in a supportive environment such as rooming-in practice and prohibiting formula use as policy, the breastfeeding rate was still high ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our experience suggests that, through training and routine monitoring, hospitals in Vietnam can apply a policy of selective episiotomy and reduce the practice, particularly among multiparous women. Global and country-specific evidence suggests that reducing unnecessary episiotomies will further improve breastfeeding rates [ 4 , 9 ]. However, key barriers to policy and practice change remain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional household survey of mothers of infants in three diverse settings in Vietnam showed a similarly high prevalence of episiotomy. Among women giving birth vaginally, 83% reported receiving an episiotomy, and those who received the procedure were significantly less likely to initiate breastfeeding within the first hour as recommended [9]. Countries in the region use different means of data collection.…”
Section: Introductionmentioning
confidence: 99%